Structure-guided design of multi-epitopes vaccine against variants of concern (VOCs) of SARS-CoV-2 and validation through In silico cloning and immune simulations. (January 2022) - Humayun, Fahad; Cai, Yutong; Khan, Abbas; Farhan, Syed Ali; Khan, Fatima; Rana, Usman Ishrat; Qamar, Anum binte; Fawad, Nasim; Shamas, Shazia; Dongqing-Wei,
Abstract: Severe Acute Respiratory Syndrome Corovirus2 (SARS-CoV-2) has been determined to be the cause of the current pandemic. Typical symptoms of patient having COVID-19 are fever, runny nose, cough (dry or not) and dyspnea. Several vaccines are available in markets that are tackling current pandemic. Many different strains of SAR-CoV-2 have been evolved with the passage of time. The emergence of VOCs particularly the B.1.351 ("South African") variant of SARS-CoV-2 has been reported to be more resistant than other SARS-CoV-2 strains to the current vaccines. Thus, the current research is focused to design multi-epitope subunit Vaccine (MEV) using structural vaccinology techniques. As a result, the designed MEV exhibit antigenic properties and possess therapeutic features that can trigger an immunological response against COVID-19. Furthermore, validation of the MEV using immune simulation and in silico cloning revealed that the proposed vaccine candidate effectively triggered the immune response. Conclusively, the developed MEV needs further wet lab exploration and could be a viable vaccine to manage and prevent COVID-19. Highlights: Prediction of SARS-CoV-2 vaccine using reverse vaccinology method. Validating Results by Molecular docking and MD simulations. In-silico cloning of vaccine construct with E. coli system was performed. Immunogenicity evaluation of Vaccine was performed using immune simulation.